Mechanistic and experimental aspects of the structural characterization of some model and real systems by Nitrogen Sorption and Mercury Porosimetry - Felipe, Carlos (2006)
Several mechanistic and phenomenological aspects of mercury intrusion and nitrogen sorption processes involving some model and real mesoporous systems were studied. The experimental pore systems examined consisted of two substrates: (a) a globular solid composed of monodisperse silica spheres in a perfect rhombohedral arrangement and (b) a controlled pore glass solid. Comparisons between the experimental nitrogen sorption and mercury porosimetry pore-size distributions demonstrated: (i) the existence of several mechanistic effects responsible of irreversible capillary behaviour that influences the calculation of pore structure parameters; (ii) the choice of the right sorption process (i.e. condensation or evaporation) suitable for comparison with either intrusion or extrusion results; (iii) the types of porous structures capable of convenient pore-size characterization by either nitrogen sorption and/or mercury porosimetry methods; and (iv) the nature of the pore entities (i.e. chambers or necks) that control the incumbent capillary process.